Resource economics - Conrad, Jon M. (Cambridge University Press, 2011)
"Resource Economics is a text for students with a background in calculus and intermediate microeconomics and a familiarity with the spreadsheet software Excel. The book covers basic concepts (Chapter 1), shows how to set up spreadsheets to solve simple dynamic allocation problems (Chapter 2), and presents economic models for fisheries, forestry, nonrenewable resources, and stock pollutants (Chapters 3-6). Chapter 7 examines the maximin utility criterion when the utility of a generation depends on consumption of a manufactured good, harvest from a renewable resource, and extraction from a nonrenewable resource. Within the text, numerical examples are posed and solved using Excel's Solver. Exercises are included at the end of each chapter. These problems help make concepts operational, develop economic intuition, and serve as a bridge to the study of real-world problems in resource management"--